Wideband, Low-Profile, Dual-Polarized Slot Antenna with an AMC Surface for Wireless Communications - Wei Hu; Rui-Na Lian; Zhao-Yang Tang; Ying-Zeng Yin (International Journal of Antennas and Propagation)
A wideband dual-polarized slot antenna loaded with artificial magnetic conductor (AMC) is proposed for WLAN/WIMAX and LTE applications. The slot antenna mainly consists of two pairs of arrow-shaped slots along the diagonals of the square patch. Stepped microstrip feedlines are placed orthogonally to excite the horizontal and vertical polarizations of the antenna. To realize unidirectional radiation and low profile, an AMC surface composed of 7 × 7 unit cells is designed underneath a distance of 0.09λ0 (λ0 being the wavelength in free space at 2.25 GHz) from the slot antenna. Both the dual-polarized slot antenna and the AMC surface are fabricated and measured. Experimental results demonstrate that the proposed antenna achieves for both polarizations a wide impedance bandwidth (return loss 10 dB) of 36.7%, operating from 1.96 to 2.84 GHz. The isolation between the two input ports keeps higher than 29 dB whereas the cross-polarization levels basically maintain lower than −30 dB across the entire frequency band. High front-to-back ratios better than 22 dB and a stable gain higher than 8 dBi are obtained over the whole band.